Bovine Tuberculosis in the Republic of Macedonia: Postmortem, Microbiological and Molecular Study in Slaughtered Reactor Cattle - Cvetkovikj, Iskra; Mrenoshki, Slavcho; Krstevski, Kiril; Djadjovski, Igor; Angjelovski, Branko; Popova, Zagorka; Janevski, Aleksandar; Dodovski, Aleksandar; Cvetkovikj, Aleksandar (Walter de Gruyter GmbH, 2017)
Bovine tuberculosis is a chronic infectious disease in cattle caused mainly by Mycobacterium bovis and to a lesser extent by Mycobacterium caprae. The other members of the Mycobacterium tuberculosis complex (MTBC) can also cause the disease in domestic and wild animals and all of them have a zoonotic potential. The main purpose of the study was to determine the presence and distribution of the tuberculous lesions in reactor cattle, and to isolate and identify the causative agents of bovine tuberculosis in the Republic of Macedonia. Lymph nodes and affected organs from 188 reactor cattle slaughtered due to a positive intradermal comparative cervical tuberculin test were analyzed by detection of tuberculous lesions, followed by isolation and molecular identification of the isolated mycobacteria. The isolation was performed on selective media - Lowenstein Jensen with glycerol, Lowenstein Jensen without glycerol and Stonebrink medium supplemented with pyruvate. The molecular identification of the MTBC members was performed by analysis of the Regions of difference (RD1, RD9 and RD4) and detection of single nucleotide polymorphisms in the lepA gene for Mycobacterium caprae. Typical tuberculous lesions were detected in 62 animals (33.0%) and the lesions were most prevalent in the mediastinal lymph nodes (47.5%). The isolated mycobacteria in the MTBC were identified as Mycobacterium bovis and Mycobacterium caprae and were found in both animals with visible lesions (82.2%) and animals without visible lesions (27.7%). The slaughterhouse postmortem examinations and laboratory investigations should be included on regular bases in order to improve the National eradication program.